An epidemiological study of oral contraceptives and breast cancer - Vessey, M P (1979)
During 1968-77, 707 women aged 16-50 years with newly diagnosed breast cancer and 707 matched controls were interviewed at eight teaching hospitals in London and Oxford about their use of oral contraceptives. Eighty-six of the patients with breast cancer were matched with controls with gall-bladder disease; these subjects were omitted from the main analyses, which thus related to 621 case-control pairs. The results were reassuring. A few statistically significant differences in oral contraceptive use were found between the breast cancer and control groups, but the data were subdivided in many ways, so that some “significant” differences would have been expected to occur by chance. The only subgroup in which the evidence for a positive association between pill use and breast cancer was at all convincing comprised women aged 46-50 years, but trends in those aged 41-45 were by and large in the opposite direction and results of combined analysis gave no cause for concern. Information on clinical stage was available for 487 patients with breast cancer treated before the end of 1975. Those who had never used oral contraceptives had appreciably more advanced tumours at presentation than those who had been using the pill during the year before detection of the lump, while past users of the pill occupied an intermediate position. This difference in staging was reflected in the pattern of survival. Oral contraceptives may have had a beneficial effect on tumour growth and spread, though diagnostic bias could not be definitely excluded.